Implementasi Sistem Penjaminan Mutu Internal (SPMI) Berbasis PPEPP dalam Meningkatkan Kinerja Guru di SMKN 2 Sangatta Utara - Fatimah Al Jahra; Indah Pratama Poluan; Salsabila Khairani; Nurfadilla Nurfadilla; Anggra Prima (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2026)
This study aims to describe the implementation of the Internal Quality Assurance System based on the PPEPP cycle in improving teacher performance at Vocational High School 2, North Sangatta. This study uses a qualitative approach with a case study type. The research subjects consisted of the principal, the quality assurance team, and 7 teachers. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions, with data validity testing through source and technique triangulation. The results of the study indicate that the implementation of the Internal Quality Assurance System based on PPEPP was carried out systematically through quality planning, program implementation, evaluation through quarterly internal audits, control, and follow-up of continuous improvement. This implementation has an impact on improving teacher performance, especially in aspects of discipline, completeness of learning tools, and compliance with standard operating procedures (SOP). However, obstacles are still found in the aspect of consistency of quality documentation and the involvement of industrial partners in supporting school programs. This study contributes in the form of a contextual implementation model of the Internal Quality Assurance System based on PPEPP in vocational schools, and can be a reference in strengthening quality culture and improving teacher performance in a sustainable manner.